Problema inverso de estimativa de temperaturas internas em chapas de aço ASTM A36 durante processo de soldagem MIG/MAG através do filtro de amostragem por importância utilizando medidas de temperatura na face oposta - Lima, Daniel Castro de (Brasil, 2022)
The arc welding process has the purpose of joining metallic parts, among them we highlight Metal Inert Gas (MIG) and Metal Active Gas (MAG). During the welding process the base material is subjected to a heat source causing an increase on temperature, inherent to the process, which changes the mechanical strength, physical-chemical properties, and metallurgical features. However, it is not possible to measure this temperature increase in the entire region of the part, only in some points by thermocouples, or external zones by means of thermographic cameras. Knowledge of the temperature field and the heat-affected zone (HAZ) is useful in achieving better weld quality. Due to the existing limitations for directly obtaining the temperature inside the plate, an inverse problem solution in heat transfer becomes attractive. Thus, the objective of this work is to estimate temperature at an internal point of an ASMT A36 steel plate during the MIG/MAG welding process using simulated temperature measurements on the face opposite the melt pool. A Bayesian approach through the Sampling Importance Resampling (SIR) filter algorithm will be used to estimate the temperature field. Known solutions for the welding problem, with Cartesian coordinates and semi-infinite medium will be adopted to represent the physical problem. The estimation was satisfactory for both the internal temperature of the plate and the heat flux estimation.